2022
DOI: 10.3390/rs14092169
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Spectral Bin Microphysics versus Bulk Parameterization in Forecasting Typhoon In-Fa (2021) before, during, and after Its Landfall

Abstract: Typhoon In-Fa hit continental China in July 2021 and caused an unprecedented rainfall amount, making it a typical case to examine the ability of numerical models in forecasting landfalling typhoons. The record-breaking storm was simulated using a 3-km-resolution weather research and forecast (WRF) model with spectral bin microphysics scheme (BIN) and two-moment seven-class bulk parameterization scheme (BULK). The simulations were then separated into three different typhoon landfall periods (i.e., pre-landfall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…(2022) and Zhang et al. (2022). For instance, abnormally high concentration of small drops occurs near the melting layer due to unrealistic melting processes, causing largely lower radar reflectivity seen in WRF simulation as compared to GPM observation (Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…(2022) and Zhang et al. (2022). For instance, abnormally high concentration of small drops occurs near the melting layer due to unrealistic melting processes, causing largely lower radar reflectivity seen in WRF simulation as compared to GPM observation (Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Except for the traditional GPM satellite data assimilation (Okamoto et al., 2016), we attempt to use GPM observations as direct constraints on model physical process. As reported by plenty of literature that parameterization of detailed microphysics processes is instrumental to LTCs forecasts (Fovell & Su, 2007; Khain & Lynn, 2011; Tao et al., 2011; Wu, Zhang, Xie, et al., 2022; Zhang et al., 2022). By using GPM satellite data to evaluate the prediction of two LTCs Lekima (2019) and In‐Fa (2021) over the Asia‐Pacific region, it is found that the WRF Double‐Moment 7‐Class (WDM7) cloud microphysics scheme (Bae et al., 2018) shows distinct advantages in LTC forecasts as compared to other microphysical parameterization schemes (Wu, Zhang, Xie, et al., 2022; Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations